2014
DOI: 10.5714/cl.2014.15.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methylene blue using lemon grass ash as an adsorbent

Abstract: Wastewater from textile industries is a major cause of water pollution in most developing countries. In order to address the issues of water pollution and high cost for treatment processes, the use of an inexpensive and environmentally benign adsorbents has been studied. The objective was to find a better alternative to the conventional methods. Lemon grass waste (ash) collected from a lemon grass stream distillation subunit in Bhutan was tested for dye removal from aqueous solutions. The study investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Additionally, a more regular structure is also observed, which indicates that the dye was uniformly adsorbed on the surface of the bioadsorbent. Similar results have been observed by other researchers [5].…”
Section: Scanning Electronic Microscopy (Sem)supporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, a more regular structure is also observed, which indicates that the dye was uniformly adsorbed on the surface of the bioadsorbent. Similar results have been observed by other researchers [5].…”
Section: Scanning Electronic Microscopy (Sem)supporting
confidence: 93%
“…. As methylene blue is a cationic dye, the -OH functional group on the surface of MP may increase the interaction between the adsorbent and the adsorbate, which contributes to the adsorption of methylene blue [5]. Also, can be observed a decrease of the intensity of the band at 1,634 cm -1 and a shifted slightly, due probably to the interaction between dye molecule and -OH and -COOH groups present on bioadsorbent surface.…”
Section: Infrared Spectrophotometry (Ft-ir)mentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have demonstrated various forms of lemongrass such as powder, ash and extracted oil residual can absorb different metal ions and dye from the aqueous solutions. 17,19,20 Only one paper regarding lemongrass dye adsorption has reported that the lemongrass ash is an efficient adsorbent for the adsorption of methylene blue from wastewater. 20 However, there is a difficulty of separating ash from the water aer dye adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…17,19,20 Only one paper regarding lemongrass dye adsorption has reported that the lemongrass ash is an efficient adsorbent for the adsorption of methylene blue from wastewater. 20 However, there is a difficulty of separating ash from the water aer dye adsorption. In this study, lemongrass was fabricated into membranes as dye absorbent to study their dye adsorption properties and resolve the separation problem of lemongrass powder or ash.…”
Section: Introductionmentioning
confidence: 99%